PRDX6AS1 gene polymorphisms and SLE susceptibility in Chinese populations - Zhang, Xiao-Xue; You, Jun-Peng; Liu, Xin-Ran; Zhao, Ya-Fei; Cui, Yan; Zhao, Zhan-Zheng; Qi, Yuan-Yuan (Frontiers in Immunology, 2022)
Background Systemic lupus erythematosus (SLE) is a complex, multisystem autoimmune disease that is characterized by the production of autoantibodies. Although accumulated evidence suggests that the dysregulation of long non-coding RNAs (lncRNAs) is involved in the pathogenesis of SLE, the genetic contributions of lncRNA coding genes to SLE susceptibility remain largely unknown. Here, we aimed to provide more evidence for the role of lncRNA coding genes to SLE susceptibility. Methods The genetic association analysis was first adopted from the previous genome-wide association studies (GWAS) and was then validated in an independent cohort. PRDX6-AS1 is located at chr1:173204199-173446294. It spans a region of approximately 240 kb, and 297 single nucleotide polymorphisms (SNPs) were covered by the previous GWAS. Differential expression at the mRNA level was analyzed based on the ArrayExpress Archive database. Results A total of 33 SNPs were associated with SLE susceptibility, with a P<1.68×10-4. The strongest association signal was detected at rs844649 (P=2.12×10-6), according to the previous GWAS. Combining the results from the GWAS Chinese cohort and our replication cohort, we pursued a meta-analysis approach and found a pronounced genetic association between PRDX6-AS1 rs844649 and SLE susceptibility (pmeta=1.24×10-13, OR 1.50, 95% CI: 1.34–1.67). The mRNA expression of PRDX6 was elevated in peripheral blood cells, peripheral blood mononuclear cells (PBMCs), and multiple cell subpopulations, such as B cells, CD4+ T cells, CD3+ cells, and monocytes in patients with SLE. The PRDX6 protein expression level was also increased in patients with SLE compared with healthy donors. Conclusion Our study provides new evidence that variants located in lncRNA coding genes are associated with SLE susceptibility.